The Influence of Talent Management, Knowledge Management, and Job Satisfaction on Employee Performance at PT Jasamarga Pandaan Tol - Eka Rahma Wulandari; Sumartik Sumartik; Vera Firdaus (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This research is a quantitative research aimed at determining and demonstrating the influence of Talent Management, Knowledge Management, and Job Satisfaction on Employee Performance in PT Jasamarga Pandaan Tol. This research utilizes the Partial Least Squares (PLS) analysis technique with the assistance of SmartPLS 3.0 software. The analysis includes validity testing, reliability testing, R-square testing, and hypothesis testing. The population and sample used in this research consist of all employees of PT Jasamarga Pandaan Tol, totaling 119 respondents. The sampling technique employed in this research is total sampling, where all members of the population are included as participants. Data collection was conducted through interviews and the distribution of questionnaires via Google Forms. The results of the testing indicate that (1) talent management has a positive and significant partial effect on employee performance, (2) knowledge management has a positive and significant effect on employee performance, and (3) job satisfaction has a positive and significant effect on employee performance. The results of this research have both theoretical and practical implications. The information provided in this research aims to enhance understanding and knowledge in the field of human resource management. It also offers insights for companies as they consider and reflect upon addressing existing issues. The findings serve as valuable input for decision-making and reflection processes. Participation in this research aims to assist the company in addressing specific issues, particularly those related to talent management, knowledge management, and job satisfaction in relation to employee performance.